(untitled) (Third Sector Social Economic Review, 2019)
It is aimed to investigate the sustainability of the current account deficit level of Turkey empirically within the framework of the model of Trehan and Walsh (1991) that using the intertemporal budget constraint. For this purpose the sustainability of the current account deficit of Turkey was examined by structural break unit root test methods for 1998:Q1- 2018:Q2 period. As a result of the study, it is determined that the current account deficit of Turkey is unsustainable. These results emphasize the importance of economic policy measures to sustain current account deficits.